Cambridge IELTS 7 : examination papers from University of Cambridge ESOL examinations : English for speakers of other languages. (Cambridge books for Cambridge exams., 2009)
This 7th collection of examination papers for IELTS provides all the exam practice you need. It contains: four complete tests for Academic candidates plus Reading and Writing modules for General Training candidates; a useful introduction to these different modules together with an explanation of the scoring system used by Cambridge ESOL; answer keys and recording scripts making it ideal for self-study; photocopiable answer sheets so you can practise transferring your answers. -- back cover.